Analisis Daily Quality Assurance (QA) / Quality Control (QC) pada Pesawat Linac di Unit Onkologi Radiasi RSUD Bali Mandara - Anak Agung Ngurah Gede Kusuma Yoga; Kadek Yuda Astina; I Wayan Juliasa (Kappa Journal, 2025)
This study focuses on evaluating the Daily Quality Assurance (QA) and Quality Control (QC) of the Linear Accelerator (Linac) machine at the Radiation Oncology Unit of Bali Mandara General Hospital (RSUD Bali Mandara). With the growing complexity of radiotherapy technology, ensuring the accuracy and consistency of radiation doses delivered during treatment is crucial for patient safety and effective cancer treatment. This study aims to evaluate the performance of the Linac Varian CX through a series of Daily checks, including output constancy, laser calibration, Optical Distance Indicator (ODI), and safety interlock systems. The results showed that the output constancy had a maximum error of ±2.5%, laser calibration deviation was within 1-2 mm, and the ODI error was within 1-2 mm, all within the tolerance limits set by the AAPM TG-40 standards. Additionally, the safety interlock and audiovisual systems were fully functional, ensuring that all safety protocols were adhered to. These findings demonstrate that the Daily QA/QC procedures implemented at RSUD Bali Mandara effectively maintain the Linac's performance within the established tolerance limits, ensuring the safety and effectiveness of radiation therapy provided to patients. This study underscores the importance of stringent QA/QC practices in radiotherapy and provides insights for potential improvements in clinical practice.